Caminhos do exílio: antirracismo e práticas emancipatórias nas trajetórias de Abdias Nascimento e Paulo Freire (1964-1981) - Teixeira, Elisa Ferreira (2021)
This work aims to analyze the trajectories of Abdias Nascimento and Paulo Freire during the period of exile (1964-1981), showing their relationship with African and Afro-Brazilian causes and projects. Therefore, I will demonstrate the experiences of these intellectuals at that time, highlighting the moments that were important for contact with the ideas, actions and subjects of these contexts, for example, there is Nascimento's participation in the pan-Africanist movement and the revolutionary actions of Freire on the African continent, and which can be found in biographies, sociological and historical studies. Furthermore, I will discuss and relate the works developed by them during this period - Pedagogy of the Oppressed (1968) and Letters to Guinea-Bissau (1978), by Paulo Freire, O quilombismo (1980) and Sitiado em Lagos (1981), by Abdias Nascimento - because through the study and comparison of these works we will be able to understand the formulations, approaches and transformations of both in their respective environments. The project's methodology is based on the use of comparative history, which in this case aims to systematically examine how the same problem crosses two distinct historical-social realities. Based on these perspectives, we will visualize narratives about contemporary colonialism and racism from the Africanist experiences of anti-racist intellectuals approached in this research, which bring to light important discussions about racial issues throughout the 20th century.